KUALITAS PELAYANAN PUSTAKAWAN PADA BADAN ERPUSTAKAAN ARSIP DAN DOKUMENTASI DAERAH PROVINSI SULAWESI TENGAH - Arisal, Andi (Katalogis, 2016)
This research aims at determining the library services quality towards the satisfaction of the visitors of Library, Archives and Documentation Board of Central Sulawesi. This type of research is a qualitative descriptive research which attempts to describe the situation or phenomenon based on the visible or noticeable facts in the Library, Archives and Documentation Board of Central Sulawesi. The selection of the informants was through purposive sampling technique in which the informants were selected with certain considerations and accidental sampling in which the informants were anyone that the researcher met or encountered accidentally. The data presented in this research were directly obtained in the field through observations, interviews, and documentations. The results of the research indicate that the library services indicators a) Tangible b) Reliability c) Assurance have not run as expected, while the indicator b) Responsiveness and e) Empathy are fairly good. Based on the results of the study showed that the quality of librariansâ€™ servicesÂ does not give statisfaction and library visitors.